2016
DOI: 10.1007/s40333-016-0047-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of transpiration between different aged black locust (Robinia pseudoacacia) trees on the semi-arid Loess Plateau, China

Abstract: Black locust (Robinia pseudoacacia) is widely planted throughout the semi-arid Loess Plateau of China. The spatial distribution of this species at different ages is highly heterogeneous due to restoration and management practices. In this study, we aimed to compare the transpiration levels between different aged black locusts at the tree and stand scales, clarifying the physiological status of this species with different ages. Black locust trees with two representative age classes (12 and 28 years) were select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 60 publications
0
23
0
Order By: Relevance
“…Accordingly, the Tr values were higher in 2016 than in 2015 in the three communities (Figure ). The ET 0 is a compound index that characterizes local meteorological conditions (Jiao et al, ), and no significant differences in ET 0 were observed between the two years. Therefore, the increased Tr between 2015 and 2016 was attributable to soil moisture primarily, and the influence of the SWC at 0–200 cm on Tr variations was greater during the drier than the wetter year for the three communities (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the Tr values were higher in 2016 than in 2015 in the three communities (Figure ). The ET 0 is a compound index that characterizes local meteorological conditions (Jiao et al, ), and no significant differences in ET 0 were observed between the two years. Therefore, the increased Tr between 2015 and 2016 was attributable to soil moisture primarily, and the influence of the SWC at 0–200 cm on Tr variations was greater during the drier than the wetter year for the three communities (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the Tr values were higher in 2016 than in 2015 in the three communities ( Figure 3). The ET 0 is a compound index that characterizes local meteorological conditions (Jiao et al, 2016), and no significant differences in ET 0 were observed between the two years.…”
Section: Run-offmentioning
confidence: 99%
“…These values are much larger than the ones (≤0.5 mm d −1 ) reported by some previous sap flow studies (Table 1) on black locust plantations [23][24][25][28][29][30]. A few studies quantified the water consumption of black locust stands in the Loess Plateau region with other methods.…”
Section: Validate the Accuracy Of The New Calibrationmentioning
confidence: 71%
“…Table 1 shows that the ratio of total sapwood area to the stand ground surface in our study was much lower than other studies for black locust stands in the Loess Plateau region. This is due to the significantly different sapwood thicknesses that were taken into account for upscaling the stand transpiration in the different studies [25,29]. Other experimenters estimated a significantly larger sapwood thickness (ranging from 5.0 to 15.4 mm) suggesting possibly no limitation to the outermost growth, which may lead to uncertainties.…”
Section: Diurnal Cycle Of Transpiration Estimated Using Granier's Orimentioning
confidence: 99%
“…Stand density is another key factor that impacts soil moisture conditions. Vegetation with higher density would more easily lead to soil desiccation due to high transpiration demand (Jiao et al, ; Wang et al, ). Therefore, the strong consumption capacity combined with high stand density contributed to the intensive consumption of soil water in black locust land, especially in the deep soil layers, where a dry layer had developed (Table and Figure ).…”
Section: Discussionmentioning
confidence: 99%